A Selective Iron(I) Hydrogenation Catalyst - Sila, Niko; Dürrmann, Andreas; Weber, Birgit; Heinemann, Frank Wilhelm; Irrgang, Torsten; Kempe, Rhett (Journal of the American Chemical Society, 2024)
Iron is the most abundant transition metal of the Earth's crust, and the understanding of its function in key technologies, such as catalysis, is highly important. We report here on an iron(I) hydrogenation catalyst. Our catalyst activates hydrogen via heterolytic bond cleavage, forms a monohydride, and hydrogenates polar double bonds via a bimetallic pathway (potassium-assisted hydride transfer). The mechanism observed seems to exclude oxidative addition and reductive elimination pathways, permitting the tolerance of numerous hydrogenation-sensitive functional groups, as demonstrated for the hydrogenation of C═O bonds.
CRIS-Team Scopus Importer:2024-10-11